2012
DOI: 10.1111/j.1468-3083.2012.04464.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tranexamic acid on melasma: a clinical trial with histological evaluation

Abstract: TXA decreased epidermal pigmentation associated with melasma and also reversed melasma-related dermal changes, such as vessel number and increased numbers of mast cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
171
2
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(187 citation statements)
references
References 20 publications
2
171
2
6
Order By: Relevance
“…TXA has also been reported to suppress neovascularization-induced bFGF [30]. In a recent clinical trial that evaluated the efficacy of systemic TXA in the treatment of melasma, we demonstrated significant decreases in the lesional melanin index and in the erythema index after the oral administration of 250 mg TXA three times per day for eight weeks [31]. Histologic analysis showed significant reductions in the level of epidermal pigmentation and vessel numbers (Figure 2A-D).…”
Section: Increased Vascularizationmentioning
confidence: 88%
See 1 more Smart Citation
“…TXA has also been reported to suppress neovascularization-induced bFGF [30]. In a recent clinical trial that evaluated the efficacy of systemic TXA in the treatment of melasma, we demonstrated significant decreases in the lesional melanin index and in the erythema index after the oral administration of 250 mg TXA three times per day for eight weeks [31]. Histologic analysis showed significant reductions in the level of epidermal pigmentation and vessel numbers (Figure 2A-D).…”
Section: Increased Vascularizationmentioning
confidence: 88%
“…Mast cells are observed more frequently in melasma skin than in non-lesional skin, especially in the dermal elastotic areas [31] ( Figure 2E-F). The median prevalence of dermal mast cells was significantly higher in melasma skin than in perilesional normal skin (173 ± 57% vs. 145 ± 57%, p=0.04) [8].…”
Section: Mast Cell Prevalencementioning
confidence: 98%
“…TXA decreases vessel numbers by antagonizing vascular endothelial growth factor (VEGF) and basic fibroblast growth factor (b FGF). Additionally it decreases mast cell numbers [50]. Trials using oral, topical and intralesional TXA in melasma and hyperpigmentation have been performed on TXA alone and in conjunction with other modalities [50][51][52][53].…”
Section: Other Botanicals As Potential Bleaching Agentsmentioning
confidence: 99%
“…Side effects were minimal and all the patients tolerated the treatment well [51]. Na et al (2012) [50] evaluated the efficacy of oral and topical TXA in melasma patients both clinically and histologically. Twenty-five melasma patients were instructed to take TXA tablets (2 tablets tds) and apply the cream twice daily for 8 weeks (each TXA tablet contained 125 mg of TXA, 50 mg of ascorbic acid, 40 mg of L-cysteine, 4 mg of calcium pantothenate and 1 mg of pyridoxine chloride.…”
Section: Other Botanicals As Potential Bleaching Agentsmentioning
confidence: 99%
“…Anti-fibrinolytic agents, such as tranexamic acid are therapeutic for melasma 96 . Li et al 97 emphasized that this plasmin inhibitor has a greater effect on the affected melasmic skin than on normal skin and that this was due to the greater amount of vasculature and mast cells in the affected skin.…”
Section: Melasma: a Model Of Incontinencementioning
confidence: 99%